Implementasi CMS untuk Website Yayasan Bina Berdaya Bangsa - Simon Prananta Barus; Prya Artha Widjaya; Jose Ryu Leonesta; Veronica Yose Ardilla; Sabrina Yose Amelia (IKRA-ITH ABDIMAS, 2023)
In community service (PKM) previously, the development of a content management system (CMS) hasbeen done for the website of the Bina Berdaya Bangsa Foundation (YBBB). The CMS that was built wasadapted to the needs of YBBB. At that time the development used a prototyping model, not yet at theimplementation phase. This is due to the time constraints of the previous PKM. Therefore, this PKM is a itscontinuation, with a focus on system implementation. In the testing phase, the CMS features are tested. In thesystem implementation phase, the activities consist of data migration, database and website installation tohosting, trial, manual writing, CMS demo, and handover process to YBBB. The Matana University PKMteam is ready to maintain the sustainability of the CMS for the YBBB website so as to improve YBBBservices.